Evaluation Method for Remaining Life of XLPE Insulated Power Cable - MA Hanchao; GAO Baoqi; LI Xiangyang; WU Suzhou; ZHANG Xiaojun (Journal of Harbin University of Science and Technology, 2023)
Aiming at the problem of low accuracy of the evaluation results due to errors in the calculation of the weight value of the evaluation factors in the evaluation of the remaining life of the cable, the remaining life evaluation method of the cross-linked polyethylene insulated power cable under the particle swarm algorithm is studied. First, the fault tree analysis method is used to determine the evaluation factors from the two perspectives of electrical aging and thermal aging, construct a remaining life evaluation model, and determine the aging coefficient of the cable. Second, the weight value and the adaptation function are calculated by the particle group algorithm, and the input data is normalized. Finally, it is determined to determine the remaining life of the cable in conjunction with different assessment factors. Through example analysis, the research method can obtain the optimal solution adaptation value 1. 982 when it is an iteration to 10 times, and in its subsequent process, the optimal solution adaptation value is stable in 1. 982. The results show that this method can obtain the optimal solution fitness value quickly, improve the efficiency of the surplus life evaluation of the analysis object, determine the weight value of the assessment factor under the measurement of the iterative period, and improve the residual life of the cable.